2020
DOI: 10.1029/2020gl091453
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐10‐Day Wave and Semidiurnal Tide Nonlinear Interactions During the Southern Hemispheric SSW 2019 Observed in the Northern Hemispheric Mesosphere

Abstract: Mesospheric winds from three longitudinal sectors at 65°N and 54°N latitude are combined to diagnose the zonal wave numbers (m) of spectral wave signatures during the Southern Hemisphere sudden stratospheric warming (SSW) 2019. Diagnosed are quasi-10-and 6-day planetary waves (Q10DW and Q6DW, m = 1), solar semidiurnal tides with m = 1, 2, 3 (SW1, SW2, and SW3), lunar semidiurnal tide, and the upper and lower sidebands (USB and LSB, m = 1 and 3) of Q10DW-SW2 nonlinear interactions. We further present 7-year com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Studies of this SSW event demonstrate a record strong quasi 6‐days wave (Q6DW) in the mesosphere‐lower thermosphere (MLT) region and low‐latitude ionosphere (Yamazaki et al., 2020), multiple dynamo processes driving the Q6DW in the ionosphere (Lin et al., 2020), propagation of the Q6DW to 25–30°N in the Asian sector and a strong longitudinal variation in the ionospheric Q6DW at low latitudes (L. P. Goncharenko et al., 2020; Gu et al., 2021; Yamazaki et al., 2020). Other features include a Q10DW in the NH MLT (He et al., 2020), a Q2DW in TEC in the Asian sector at low latitudes, and quasi‐semidiurnal disturbances in TEC at low latitudes (L. P. Goncharenko et al., 2020). Here we utilize a variety of observational data to demonstrate that this Antarctic SSW produced anomalies in the middle‐latitude thermosphere and ionosphere in the NH and to suggest mechanisms responsible for these anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this SSW event demonstrate a record strong quasi 6‐days wave (Q6DW) in the mesosphere‐lower thermosphere (MLT) region and low‐latitude ionosphere (Yamazaki et al., 2020), multiple dynamo processes driving the Q6DW in the ionosphere (Lin et al., 2020), propagation of the Q6DW to 25–30°N in the Asian sector and a strong longitudinal variation in the ionospheric Q6DW at low latitudes (L. P. Goncharenko et al., 2020; Gu et al., 2021; Yamazaki et al., 2020). Other features include a Q10DW in the NH MLT (He et al., 2020), a Q2DW in TEC in the Asian sector at low latitudes, and quasi‐semidiurnal disturbances in TEC at low latitudes (L. P. Goncharenko et al., 2020). Here we utilize a variety of observational data to demonstrate that this Antarctic SSW produced anomalies in the middle‐latitude thermosphere and ionosphere in the NH and to suggest mechanisms responsible for these anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of ionospheric dynamics to this extreme event have been observed in both hemispheres, such as the quasi‐6‐day waves (Q6DWs) and quasi‐10‐day waves (Q10DWs; Goncharenko et al., 2020; Lin et al., 2020; Wang et al., 2021). The unusual Q10DWs in the MLT region in both hemispheres are found to be triggered by the extreme Antarctic SSW (Eswaraiah et al., 2020; He et al., 2020; Lee et al., 2021). The Q6DWs are also observed by meteor radars from the middle latitudes in the Southern Hemisphere to the equatorial region in the Northern Hemisphere, which is suggested to be caused by the equatorward propagation of Q6DWs due to the extreme Antarctic SSW (Lee et al., 2021; Liu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the excitation mechanism of the global enhanced Q6DWs is still unclear, especially at the middle latitudes in the Northern Hemisphere. For instance, the enhancement of Q6DWs observed by a meteor radar over Mohe (53.5°N) is attributed to the seasonal variations (He et al, 2020), while Yamazaki et al (2020) speculated that the Q6DWs in the Northern Hemisphere might be related to the 2019 Antarctic SSW. The contributions of the seasonally enhanced Q6DWs have not been evaluated specifically during the 2019 Antarctic SSW and the complex process of the global enhanced Q6DWs still needs to be clarified.…”
mentioning
confidence: 99%
“…Consequently, the association of 10DWs with SSW events has received some attention over the past two decades (Palo et al, 2005;Yu et al, 2019;Yamazaki & Matthias, 2019;He et al, 2020;Luo et al, 2020;Wang et al, 2021), with researchers nding that enhanced 10DWs are closely related to SSW. Ultimately, the abovementioned studies demonstrated that the 10DW eld in the stratosphere and above is dominated by modes with small zonal wavenumbers, i.e., W1, W2, E1 and E2.…”
Section: Introductionmentioning
confidence: 99%